Gastroschisis: five cases after primary closure at Sanglah General Hospital, Bali, Indonesia - Nyoman Gina Henny Kristianti; I Wayan Darma Artana; I Made Kardana; Putu Junara Putra; Made Sukmawati; Kadek Deddy Ariyanta; Made Darmajaya (Intisari Sains Medis, 2020)
Background: Gastroschisis is a congenital anterior abdominal wall defect characterized by intra-abdominal organs evisceration without covering the membrane. Several risk factors affect the outcome of a gastroschisis patient. Considering these risk factors might also increase the chance of better prognosis and survival. We report five neonates with gastroschisis after primary closure in Sanglah General Hospital, Denpasar, Bali, in 2017. This case series aims to describe the clinical characteristics and outcome of different babies with gastroschisis managed by primary closure surgery.Case Presentation: Four of our cases were detected during pregnancy with fetal gastroschisis at the age of 32, 19, 23, 25 weeks of gestation, respectively. We reserve cesarean delivery for the patient who did antenatal care in our hospital, but one of our patients was born by spontaneous labor due to lack of antenatal care. Four cases had the primary closure of less than 2 hours and one of them after 10 hours. Good outcome was found in three cases that started enteral feeding on the 7th day after post closure. Other cases started oral feeding on the 3rd day and 12th day—both of them shown poor outcomes. Three cases survive, but two others died because of sepsis.Conclusion: We found poor outcomes in both cases, which neonatal sepsis as a significant cause. One of our cases with poor outcome was referred from another hospital without antenatal care and had a long duration of entering the operating room. Diagnosing these babies in their early prenatal period and transferring them to an experienced medical centre containing multidisciplinary working facilities will contribute to both the mother and the baby's health.